Ethylcellulose/Ag nanowire composites as multifunctional patchable transparent electrodes - Kim, Sunho; Lee, Hyunho; Kim, Daekyoung; Ha, Heebo; Qaiser, Nadeem; Yi, Hyunjung; Hwang, Byungil (ELSEVIER SCIENCE SA, 2020)
Cellulose and its derivatives are attractive for the development of electronic devices because they are naturally abundant and biodegradable. Ethyl cellulose (EtC) is particularly promising as a substrate material for flexible electronics because it is waterproof with low air permeability and high transparency. In this study, adaptable EtC-Ag nanowire (AgNW) composite-based transparent electrodes (TEs) are developed for various electronic devices. Fabrication of EtC-AgNW composites is clean and safe without using toxic chemicals, resulting in highly transparent and conductive electrodes. With the assistance of functional tapes, EtC-AgNW composites are successfully used as attachable flexible transparent interconnects, and sensing electrodes for transparent electrophysiological sensors. In addition, a semitransparent perovskite solar cell is demonstrated by using the EtC-AgNW composites as a top electrode, which shows a high power conversion efficiency of 7.03%.
Keywords: CELLULOSE; GRAPHENE